Analisis Pengaruh Rasio Profitabilitas Terhadap Tingkat Kemampuan Pengeluaran Zakat Pada BUSN Devisa - ZIDNY, M. ZIDNY NAFI' HASBI; M. Zidny Nafi' Hasbi; Amin, Mohammad (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2021)
Islamic banking is a representation of the Islamic economic system that confirms explicitly and firmly the social orientation within it. One such social function is zakat. In sharia banks, the orientation of zakat is directly proportional to the profitability of the company due to increase the zakat ability of sharia bank, first improve its profitability. The purpose of this study is to analyze the influence of Profitability Ratio to the level of zakat expenditure capability in Sharia Bank Foreign exchange with proxy from Profitability Ratio is Return On Asset (ROA) and Return On Equity (ROE). Data from this research comes from Annual Report of PT. Bank Muamalat Indonesia, PT. Bank BNI Syariah, PT. Bank Syariah Mandiri and PT.Bank Mega Syariah from 2014 until 2017. As for the variable of research used is Zakat as dependent variable while independent variable is Return On Asset (ROA) and Return On Equity (ROE). This study uses panel data regression using Eviews 9 as an analytical tool. After the analysis, this study proves that Return On Asset does not affect the ability of zakat expenditure, while Return On Equity affect the ability of zakat expenditure.